The business of bodies: Ethical perspectives on for‐profit body donation companies. Issue 1 (23rd November 2015) - Champney, Thomas H.
Abstract : Human cadavers are a scarce resource that have educational, research and clinical value. While the tissues have great value, it is illegal in many countries to pay for them. In the United States, a number of for‐profit body acquisition companies have been established over the past decade. These companies obtain bodies which were freely donated by the individuals or their families. The companies distribute the specimens to surgical training organizations, researchers and educational institutions. These businesses do not charge the receiving organizations for the bodies; they do, however, charge a fee that covers the transport, handling and other services which creates a profit for their companies. These types of businesses are described and analyzed as to whether they constitute an ethically appropriate mechanism to obtain and distribute bodies. The role of organizations and governments in establishing policies and regulations for the appropriate treatment of human remains is addressed. Recommendations are given for best practices in the ethical use and regulation of willed bodies. Clin. Anat. 29:25–29, 2016. © 2015 Wiley Periodicals, Inc.